Impact of tellurium as an anion dopant on the photovoltaic performance of wide-bandgap Cu(In,Ga)Se2 thin-film solar cells with rubidium fluoride post-deposition treatment - Ağca, S.; Çankaya, G.; Sonmezoglu, S. (Frontiers in Energy Research, 2023)
Development of wide-bandgap Cu(In,Ga)Se2 thin films is crucial for achieving the theoretical Shockley-Queisser limit values in single-crystal solar cells. However, the performance of solar cells based on wide-bandgap thin film absorbers is significantly lagging their counterparts in the narrow-bandgap absorber thin films. Herein, we develop a feasible strategy to improve photovoltaic performance of wide-bandgap Cu(In,Ga)Se2 chalcopyrite thin film solar cells by doped with simultaneously both RbF PDT and Te2- anion as dopants into absorber layer during the three-stage co-evaporation process. Besides exhibiting significant change on the GGI gradient, the synergistic effect of Te2- anion dopant is quite beneficial to control grain size, defects in grain boundaries and charge carrier lifetime for encouraging charge separation and extraction, which contributes to simultaneously boosting short-circuit current density and fill factor. Te-poor-based devices afford an impressive efficiency of 9.58% compare to control ones of 6.43%. More importantly, the highest efficiency and Voc values for wide-bandgap based thin film solar cells containing Te anions were achieved compared to their counterparts in the literature. These results demonstrate the role of Te2- anion in wide-bandgap absorber thin films on photovoltaic performance of thin film solar cells and its potential in reasonable and effective ways for highly efficient wide-bandgap thin film solar cells.